Getting to the Heart of Left–Right Asymmetry: Contributions from the Zebrafish Model - Kelly A. Smith; Veronica Uribe (Journal of Cardiovascular Development and Disease, 2021)
The heart is laterally asymmetric. Not only is it positioned on the left side of the body but the organ itself is asymmetric. This patterning occurs across scales: at the organism level, through left–right axis patterning; at the organ level, where the heart itself exhibits left–right asymmetry; at the cellular level, where gene expression, deposition of matrix and proteins and cell behaviour are asymmetric; and at the molecular level, with chirality of molecules. Defective left–right patterning has dire consequences on multiple organs; however, mortality and morbidity arising from disrupted laterality is usually attributed to complex cardiac defects, bringing into focus the particulars of left–right patterning of the heart. Laterality defects impact how the heart integrates and connects with neighbouring organs, but the anatomy of the heart is also affected because of its asymmetry. Genetic studies have demonstrated that cardiac asymmetry is influenced by left–right axis patterning and yet the heart also possesses intrinsic laterality, reinforcing the patterning of this organ. These inputs into cardiac patterning are established at the very onset of left–right patterning (formation of the left–right organiser) and continue through propagation of left–right signals across animal axes, asymmetric differentiation of the cardiac fields, lateralised tube formation and asymmetric looping morphogenesis. In this review, we will discuss how left–right asymmetry is established and how that influences subsequent asymmetric development of the early embryonic heart. In keeping with the theme of this issue, we will focus on advancements made through studies using the zebrafish model and describe how its use has contributed considerable knowledge to our understanding of the patterning of the heart.